Efficacy and safety of Puerarin injection on acute heart failure: A systematic review and meta-analysis - Li, Zunjiang; Fan, Ye; Huang, Chunxia; Liu, Quanle; Huang, Manhua; Chen, Baijian; Peng, Zhe; Zhu, Wei; Ding, Banghan (Frontiers in Cardiovascular Medicine, 2022)
Objective This study aimed to assess the adjunctive efficacy and safety of Puerarin injection (PI) on acute heart failure (AHF) based on a systematic review and meta-analysis. Methods Nine databases were searched from March 1990 to March 2022 to identify randomized controlled trials (RCTs) related to the adjunctive treatment of PI for AHF. The Cochrane collaboration tool was used to assess the risk of bias in the included studies. Meta-analysis and subgroup and sensitivity analyses were conducted by RevMan 5.3 software. The evidence’s certainty was evaluated by grading recommendations assessment, development, and evaluation (GRADE) methods. Results A total of 8 studies were included with a total of 614 patients with AHF. The meta-analysis demonstrated that adjunctive treatment with PI on AHF was superior to conventional medicine alone. It increased the total effective rate (RR = 1.38; 95% CI, 1.22–1.55; p < 0.001) and improved left ventricular ejection fraction [SMD = 0.85; 95% CI (0.62, 1.09); p < 0.001]. Regarding safety, a total of 11.9% (23/194) adverse reactions were observed in the PI group and 9.8% (19/194) adverse reactions in the control group, and there were no significant differences in the incident rate of adverse events between both groups [RR = 1.16; 95% CI (0.66–2.05); p = 0.061]. The outcomes’ evidentiary quality was assessed as “moderate.” Conclusion PI had an adjunctive effect on AHF combined with conventional medicine, and it seemed to be safe and more effective than the conventional medical treatment alone for improving the total clinical effective rate and left ventricular ejection fraction. But further well-designed RCTs are required to confirm the efficacy and safety of XBP in treating AHF due to the poor methodological quality of the included RCTs. Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=327636], identifier [CRD42022327636].